Elder Care in Occupational Therapy - Lewis, Sandra Cutler, ....- (Thorofare (N.J.) : Slack, 2003)
Elder Care in Occupational Therapy has been extensively revised into a new and completely updated second edition. This pragmatic text presents up-to-date information in a user-friendly format that seamlessly flows from one subject to the next. From wellness to hospice, Elder Care in Occupational Therapy, Second Edition offers a broad yet detailed discussion of occupational therapy practice that is devoted to older adults. A wide variety of topics are covered in a concise format, such as historical perspectives, theoretical insights, the aging process, and current interventional strategies, to name a few. Twenty informative appendices are also included that clarify issues such as Medicare coverage, community and clinical living arrangements, client-centered practice, exercise programs, evidence-based practice, and a summary of the newly adopted Occupational Therapy Practice Framework: Domain and Process.
Keywords: Ergotherapie -- Ouderen; Geriatrie; Ouderenzorg